Mengapa Aku Berbakat? Pandangan Anak Berbakat Tentang Dirinya - Tjahjono, Evy (ANIMA Indonesian Psychological Journal, 2002)
The unique gifted-child characteristics led to unique life expectancies in their interaction with the environment. The environment's reaction against the gifted child characteristics manifestation affects the susceptibility of the gifted child towards socio-economical and personality problems, especially concerning his/her self-concept. Some important factors influencing personality development of the gifted child are: confusing identity, imbalanced development, isolation, conflict between friendship and actualization, perfectionism, and various worries due to excessive emotional sensitivity. Some ways are proposed to help gifted children to gain a positive self-image, among others: creating positive experience through interaction with the environment, appreciating individual differences, encouraging opportunities to actualization, offering realistic goals and exposing to challenges according to their potentials.